2004
DOI: 10.1088/0953-4075/37/5/l03
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of a K-shell vacancy in atomic carbon created by 1s   2p photoexcitation of C+

Abstract: Lifetimes for K-shell vacancy states in atomic carbon have been determined by measurement of the natural linewidth of the 1s → 2p photoexcited states of C + ions. The K-shell vacancy states produced by photoionization of atomic carbon are identical to those produced by 1s → 2p photoexcitation of a C + ion: 1s2s 2 2p 2 2 D, 2 P, and 2 S autoionizing states occur in both cases. These vacancy states stabilize by emission of an electron to produce C 2+ ions. Measurements are reported for the lifetime of the 1s2s 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 30 publications
12
70
0
Order By: Relevance
“…and R K is a double radial integral defined as [86], and possibly fortuitously agrees somewhat better with our calculated value (≈10 fs) than with Ref. [47] (≈14 fs).…”
Section: Auger Decay Processsupporting
confidence: 91%
“…and R K is a double radial integral defined as [86], and possibly fortuitously agrees somewhat better with our calculated value (≈10 fs) than with Ref. [47] (≈14 fs).…”
Section: Auger Decay Processsupporting
confidence: 91%
“…This approximation is better for cases of core excitation of nuclei with fast Auger relaxation rates, as well as for heavier nuclei that experience unscreened fields. With light species, such as deuterons or protons, this geometry change during the B6 fs carbon 1s core-hole lifetime 45 may not be negligible. Gadea et al 41 suggested that a similar mechanism may play a role in core-to-valence excitation of acetylene.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of deep-inner-shell photoabsorption by atomic cations and anions has been provided recently by Müller (Müller 2015). Experimental data on K-shell photoionization and photoexcitation of positive ions with atomic numbers  Z 3 have been published for Li +  (Carroll & Kennedy 1977;Kiernan et al 1994;Mosnier et al 2000;Scully et al 2006), Be +  (Mehlmann & Esteva 1974), B + (Müller et al 2014), B 2+ (Müller et al 2010a), C + (Schlachter et al 2004;Müller et al 2015), C 2+ (Scully et al 2005), C 3+ (Müller et al 2009), N + (Gharaibeh et al 2011), N 2+ (Gharaibeh et al 2014) (Rudolph et al 2013;Steinbrügge et al 2015), Fe 24+ (Rudolph et al 2013), and Kr 34+ . K-shell photoionization experiments with neutral neon atoms have employed static gas targets, and a large body of papers has addressed specific features in the excitation and decay of K-shell vacancies in neon atoms.…”
Section: Introductionmentioning
confidence: 99%